Profiling and Enhancing Scientific Literacy in Disaster Mitigation: The Effectiveness of the Discovery Learning Model for Elementary School Teacher Education Students - Anggit Grahito Wicaksono; Mukhlis Mustofa; Daru Angga Amirullah (Jurnal Penelitian Pendidikan IPA, 2025)
The critical need for effective pedagogical interventions to address Indonesia's declining scientific literacy, especially within its disaster-prone context, drives this study, which aims to investigate the effectiveness of the discovery learning model in enhancing the scientific literacy of elementary school teacher education (PGSD) students within disaster mitigation contexts. Employing a mixed-methods sequential explanatory design with 32 participants, data were collected via a pretest-posttest using a validated scientific literacy test measuring three PISA competencies and analyzed descriptively, with paired t-tests, N-gain scores, and thematic analysis. Results indicated a significant quantitative improvement (p < 0.05) as mean scores rose from 53.28 to 72.50 with a moderate N-gain of 0.411, while qualitative findings revealed enhanced engagement and critical thinking, albeit with persistent challenges in translating theoretical knowledge into practical application, particularly in the competencies of explaining phenomena and using evidence. It is concluded that structured discovery learning significantly enhances scientific literacy among pre-service teachers when contextualized within authentic scenarios, underscoring its essential role in teacher education for disaster-prone regions like Indonesia and recommending the incorporation of applied learning experiences to effectively bridge the theory-practice gap in science education.